Design A Hybride-Based Outpatient Medical Record System at RSU Menteng Mitra Afia - Jourdy; Fauziyah; Bernadus Gunawan Sudarsono (Yayasan Bina Internusa Mabarindo, 2022)
Menteng Mitra Afia Hospital is known as a specialist hospital for neurology and psychiatry. Over time, following the development and needs of its customers, then turning itself into a general hospital. In the process of recording medical records, Menteng Mitra Afia General Hospital still uses the conventional method by recording data (patient data, doctor data, nurse data, and room data) through book media which is still difficult for hospital staff. Likewise, the outpatient registration process for patients is always crowded and overcrowded just to register at the polyclinic. Applications made using the PHP programming language and Native Hybrid with My Sql database and using the CSS framework. The system is designed using a database, is expected to help and facilitate the process of inputting medical record data, so that it can provide solutions to the outpatient medical record process and can provide convenience in the reporting process so as to support the provision of fast and accurate information and data can be stored safely.